World economy in 90's - "Bhalla, V. K." (New Delhi, 1990)
The World Economy In The 1990S Is Facing Exciting Challenges And Opportunities With Global Transformation Of Historic Dimensions. The Us Is No More In A Position To Dictate But Can Still Lead As A Major Player In World Trade, Finance And Investment Relationships. An Integrated Europe, Led By A Unified Germany, Will Be The World S Largest Market. Japan Is Already The World S Main Creditor And Leads In Key Technologies. The Reforms In The Soviet Union And Eastern Europe Have Ended The Cold War, The Word Economy Is Becoming Increasingly Inter-Dependent And Competitive In A Multi-Polar World. A Main Element In This Process Is The Role Of Direct Investment Funds Moving Across National Boundaries. In Recent Years, Fdi Flows Have Been Of The Order Of Dollar 150-175 Bn. A Year. There Need To Be Some Sensible Norms In Regards To Capital Flows If They Are To Prove Highly Beneficial And Be Welcome In Developing Countries.A Central Question For The 1990S Is Whether The New Structure Of International Relations Will Generate Conflict Over Trade Issues Or Healthy Competition. If Usa, Japan And An Integrated Europe Coordinate Their Policies In A Forward-Looking Manner, And Desist From Protectionist Measures, Then This Would Facilitate World Economic Development And Trade. This Process Can Be Helped Forward If The Multilateral Institutions Also Act With Vision And Firmness.The Book Reviews Established Policy Pattern Towards Transnational Corporations And Attempts To Evaluate The Corporations And Attempts To Evaluate The Complexities Of Exposure Management. The Present Study Deals Not Only With Foreign Direct Investment And Portfolio Investment In The Evolving International Monetary And Financial System, But Also Contributes To A Better Understanding Of The Opportunities And Dangers In Terms Of Certain Key Issues For The World Economy In 90S : Sustaining The Economic Upswings Of The 80S In The Industrial Countries: Integrating The Centrally Planned Economies Into The World Economy; Fostering Open And Diversified International Capital Markets; Dealing With The External Debt Problem; And Giving Greater Attention To Development And To The World S Poor.
Keywords: Economics